The development of learning media and critical thinking skill instrument based on 5E learning cycle model on harmonic vibration material - Malahayati Rahayu Sulastri; Jannatin Ã¢â¬ËArdhuha; Muhammad Zuhdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to produce products in the form of learning media and instruments based on the 5E learning cycle model on harmonic vibrationÃÂ material. It isÃÂ development research usingÃÂ the ADDIE model consisted of 5 stages:ÃÂ analysis, design, development, implementation, and evaluationÃÂ stagesÃÂ (this study wasÃÂ limited to the development stage). The products developed were Syllabus, Lesson Plan, Student Worksheets, and Critical Thinking Skill Instruments in Physics. The feasibilityÃÂ of the learning mediaÃÂ and instrument developed was measuredÃÂ by three expertsÃ¢â¬â¢ validation by calculating the validity and reliability values of the media and instrument. The validity results basedÃÂ on the expertsÃ¢â¬â¢ assessment showed that the score of the syllabus wasÃÂ 3.70 with very valid criteria. The Lesson PlanÃÂ was 3.66 withÃÂ very valid criteria; the LKPD wasÃÂ 3.66 withÃÂ very valid criteria, and the Critical Thinking Skill Instrument in Physics wasÃÂ 3.63 included in the very valid criteria. The reliability results of the syllabusÃÂ were 94.52%, the Lesson PlanÃÂ was 90.36%, the LKPDÃÂ was 91.78%, and the Critical Thinking Skill Instrument in Physics wasÃÂ 93.62%, indicating that all aspects assessed hadÃÂ a reliable category. BasedÃÂ on these results, it can be concludedÃÂ that the learning media and instrument developed are feasibleÃÂ to use in learning to improve students' critical thinking skills in Physics on harmonic vibrationsÃÂ material.